Aluminum, a Friend or Foe of Higher Plants in Acid Soils - Bojórquez-Quintal, Emanuel; Escalante-Magaña, Camilo; Echevarría-Machado, Ileana; Martínez-Estévez, Manuel (Frontiers in Plant Science, 2017)
Aluminum (Al) is the most abundant metal in the earth's crust, but its availability depends on soil pH. Despite this abundance, Al is not considered an essential element and so far no experimental evidence has been put forward for a biological role. In plants and other organisms, Al can have a beneficial or toxic effect, depending on factors such as, the concentration of the metal, the chemical form of Al, growth conditions and plant species. Here we review recent advances in the study of Al in plants at physiological, biochemical and molecular levels, focusing mainly on the beneficial effect of aluminum in plants (stimulation of root growth, increased nutrient uptake, the increase in enzyme activity, etc.). In addition, we discuss the possible mechanisms involved in improving the growth of plants cultivated in soils with acid pH, as well as mechanisms of tolerance to the toxic effect of aluminum.